Analysis of Geoid and Sea Level in the Area of the JASON-1 Calibration Campaign, IBIZA 2003 - Martínez Benjamín, J.J.; Rodríguez Velasco, G.; Sevilla, M.J. (Física de la Tierra, 2005)
Actual studies related to calibration of altimeters involves the use of GPS buoys and other systems for the determination of absolute bias in just purely geometric sense. Doing so it seems to be avoided the estimating a marine geoid or the mean sea surface. However, this is not at all true. On the one hand, we need the cross track sea level gradient in order to account the difference in the distance between the altimeter ground track and the position of the point to use in the comparison. On the second hand, an accurate estimation of the surface slope is also needed for linking offshore altimetric data and coastal tide gauges. This is the followed method used to process the Spanish/French JASON-1 calibration campaign, IBIZA 2003. This campaign took place in June 9th-17th, 2003. The area, close to a big island and in a singular place from a dynamic point of view, has a complex local geoid and mean sea surface around. For this reason, in this paper we present some comparisons and correlations between results from this campaign data and some previous results about geoid and mean sea surface in the area, completely independent (in time, and in the kind of data employed: gravimetry or satellite altimetry). The compared surfaces have been some mean sea surface models over the area and local marine geoids, built up from gravimetry and altimetry of ERS ESA satellite, with a higher spatial resolution.